2008
DOI: 10.1111/j.1745-7254.2008.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide regulates lung tissue-oxidized glutathione and total antioxidant capacity in hypoxic pulmonary hypertensive rats

Abstract: Aim: To investigate the modulatory effect of sudium hydrosulfide on lung tissue‐oxidized glutathione and total antioxidant capacity in the development of hypoxic pulmonary hypertension (HPH). Methods: After 21 d of hypoxia, the mean pulmonary artery pressure was measured by cardiac catheterization. The plasma H2S level and production of H2S in the lung tissues were determined by using a spectrophotometer. The lung homogenates were assayed for total antioxidant capacity (T‐AOC), superoxide dismutase (SOD), oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 27 publications
1
78
0
Order By: Relevance
“…Along the same line, Wei et al (48) showed that severe oxidative stress was present in a model of hypoxic pulmonary hypertension and was accompanied by a decrease in the endogenous production of H 2 S in the lung tissue. H 2 S, however, acted as an antioxidant during this oxidative stress, which was a result of the attenuated GSSG content.…”
Section: K Wt 2k Wtmentioning
confidence: 79%
See 1 more Smart Citation
“…Along the same line, Wei et al (48) showed that severe oxidative stress was present in a model of hypoxic pulmonary hypertension and was accompanied by a decrease in the endogenous production of H 2 S in the lung tissue. H 2 S, however, acted as an antioxidant during this oxidative stress, which was a result of the attenuated GSSG content.…”
Section: K Wt 2k Wtmentioning
confidence: 79%
“…It is reported that H 2 S is involved in the regulation of vascular tone (24) and hypertension (52) and protects neuronal cells from oxidative stress by increasing the intracellular concentration of antioxidant and GSH (19,48). Recently, Tripatara et al (44) demonstrated that generation of endogenous H 2 S limits renal ischemia/reperfusion injury and dysfunction.…”
Section: K Wt 2k Wtmentioning
confidence: 99%
“…Alternatively, the increased plasma and urinary H 2 S levels in diabetic-treated rats suggests that exogenous H 2 S might have improved endothelial function due to its reducing oxidative stress property as it has been reported to be a potent antioxidant molecule. 51,52 Nevertheless, the above hypothesis deserves further verification.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that part of the vasculoprotective effects may be due to inhibition of platelet aggregation [96] [11,[23][24][25][26] [21,22,30,114] …”
Section: ; This Suggests That There Is a Possible Loss Of H2s Synthesmentioning
confidence: 99%